The impact of cement sheath mechanical properties on near wellbore hydraulic fracture initiation - Fallahzadeh, S.; Rasouli, Vamegh (ISRM, 2012)
Hydraulic fracturing is a stimulation technique which is used, in particular in unconventional reservoirs such as shale gas and tight sandstones, in order to en-hance production of hydrocarbon. Hydraulic fracturing is usually operated through the perforations in cased-hole wellbores. The perforation tunnels cut the casing and cement sheath filled the annulus space between the casing and the wellbore wall to communicate the formation to the wellbore. The near wellbore condition is significantly important as the hydraulic fracture crosses this zone after its initiation from the wellbore wall. The presence of casing is considerably important in terms of stress distribution around the wellbore. Also, the quality of the cement sheath may affect the initiation of an induced fracture and the geometry of propagated fracture plane around the wellbore wall. In this study a generic model was developed to analyze the wellbore stress distribution, considering the effects of casing and cement sheath. The effect of various properties of cement, including Poisson’s ratio, elasticity modulus, thermal expansion coeficent, Biot’s constant and permeability, on fracture initiation were investigated. In this model analytical equations were applied and numerical simulations were performed to estimate the stress profile around a cased cemented borehole with arbitrary inclination and azimuth. This model allows studying the fracture initiation in a cased perforated wellbore. The model was applied to the data from a real wellbore and good results were obtained.